PENGARUH MODEL PEMBELAJARAN TYPE TWO STAY TWO STRAY DAN MINAT BELAJAR TERHADAP HASIL BELAJAR EKONOMI PADA SISWA KELAS X SMA DIAN ANDALAS - PADANG - Hasmaynelis Fitri; Yunia Wardi (Program Magister Pendidikan Ekonomi (S2), 2015)
This study aims to find: (1). The results of the economic study which has high and low learning interest are taught using learning model two stay two stray higher than the use of conventional learning model, and (2). Interaction between the use of models of learning and students' interest in learning the results of the economic study. This type of research is experimental treatment by block, using two classes of experimental class is a class X.1 to X.2 control class is class, with a total sample of 55 students. Data collection techniques for interest in learning is done by spreading the research questionnaire before learning process is done. As for the results of such study in the form of multiple-choice test given at the end of the lesson. Data analysis techniques in the study include test requirements normality test and homogeneity test, while the results of hypothesis testing includes independent test samples T-test and two-way ANOVA. Results of this study concluded that: (1). Economic learning outcomes of students who are taught by learning model two stay two stray significantly higher than students taught by conventional learning models, (2). Economic learning outcomes of students who have a high interest in learning taught by learning model two stay two stray significantly higher than students taught by conventional learning models, (3). Economic learning outcomes of students who have low learning interest taught by learning model two stay two stray significantly higher compared to using conventional learning models and (4). There is no interaction between the cooperative learning model two stay two stray and interest in learning on learning outcomes of students. Keywords: cooperative learning model two stay two stray, interest in learning and learning outcomes